Poverty and time - Walter Bossert; Satya R. Chakravarty; Conchita d' Ambrosio (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
We examine the measurement of individual poverty in an intertemporal context. Our aim is to capture the importance of persistence in a state of poverty and we characterize a corresponding individual intertemporal poverty measure. Our first axiom requires that intertemporal poverty is identical to static poverty in the degenerate single-period case. The remaining two properties express decomposability requirements within poverty spells and across spells in order to reflect the persistence issue. In addition, we axiomatize an aggregation procedure to obtain an intertemporal poverty measure for societies and we illustrate our new index with an application to EU countries.
Keywords: C43; D63; I32; 330; Intertemporal poverty measurement; equity